THE INFLUENCE OF DRUMBAND EXTRACURRICULAR ACTIVITIES ON STUDENTS’ MUSICAL INTELLIGENCE IN ELEMENTARY SCHOOLS - Nur Laili,; Zudan Rosyidi, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Extracurricular activities are great ways to discover and develop students’ creativity, talents, and interests. Drumband extracurricular activities in elementary schools offer several benefits, including increasing musical intelligence, which has the potential to have a positive impact on students’ development. This study aimed to determine the effect of after-school drumband activities on the musical intelligence of elementary school students. Musical intelligence is the ability to think about music, such as recognising, remembering, hearing, and even manipulating musical patterns. This research used qualitative approach with a Systematic Literature Review (SLR) design. Data were analyzed using PRISMA analysis technique. Research results indicated that after-school drumband activities effectively increased elementary school students' musical intelligence. These activities provide an outlet for students' interests and talents in music, and help them develop their skills and abilities. Overall, extracurricular drumband activities offer valuable opportunities for students to discover and nurture creativity, talent and interest in music.